Analisis Keberlanjutan Inovasi Lokal : Studi Kasus Inovasi e-Health Cimalaka Sehat - Ramdani, Endah Mustika (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
Innovation in public services is a demands , both for central and local governments to improve services to the community. In service innovations at the local level, it certainly brings the risk of rejection from people who are not ready to change. This study aims to examine the local innovations in the health sector, Cimalaka Sehat e-health innovation case studies. The method used is descriptive qualitative with a case study at the Innovation of e-health Cimalaka Sehat services as a pioneer of e-health innovations in the Sumedang Regency. The technique of determining informants uses purposive sampling, data collection is done by observation, in-depth interviews, and documentation. The results showed that in innovation healthy cimalaka e-health has many advantages for the community through changing processes from manual to online as well as increasing features of health services that support the development of health services for puskesmas. However, from several advantages, there are several constraints and problems including the lack of a thorough understanding of the usefulness of innovation, low commitment and consistency of service providers to adapt to available innovations, with indications that the organizers are in a comfort zone that is providing alternative services similar to the innovation e-health (service through WhatsApp), which actually reduces the value of the usefulness of innovation, so that people are reluctant to change to existing service innovations.